2022
DOI: 10.3171/2021.12.spine211176
|View full text |Cite
|
Sign up to set email alerts
|

Lateral versus prone robot-assisted percutaneous pedicle screw placement: a CT-based comparative assessment of accuracy

Abstract: OBJECTIVE Single-position lateral lumbar interbody fusion (SP-LLIF) has recently gained significant popularity due to increased operative efficiency, but it remains technically challenging. Robot-assisted percutaneous pedicle screw (RA-PPS) placement can facilitate screw placement in the lateral position. The authors have reported their initial experience with SP-LLIF with RA-PPS placement in the lateral position, and they have compared this accuracy with that of RA-PPS placement in the prone position. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Moreover, emerging innovations, like robotic spinal surgery and the growing popularity of LLIF, emphasize the potential of PPS insertion in the lateral decubitus position [27][28][29]. The LLIF approach is versatile and suitable for various degenerative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, emerging innovations, like robotic spinal surgery and the growing popularity of LLIF, emphasize the potential of PPS insertion in the lateral decubitus position [27][28][29]. The LLIF approach is versatile and suitable for various degenerative conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, current studies differ in terms of whether changes in position have an effect on screw accuracy, and in an analysis of the accuracy of 453 screws in 78 patients who received lateral placement in the prone position by Okuda, Ryuichiro et al showed no statistically significant conceptual difference from the prone group 19 . A meta‐analysis by Keorochana et al showed no statistically significant difference between the lateral and prone positions in terms of intraoperative blood loss, radiotherapy dose, lumbar lordosis, incidence of complications, or need for reoperation, 20 while a study by Fayed et al showed that lateral position nailing had a higher error rate 21 . In addition, most studies used only postoperative CT as a criterion for the presence and extent of bias.…”
Section: Discussionmentioning
confidence: 99%
“…showed no statistically significant difference between the lateral and prone positions in terms of intraoperative blood loss, radiotherapy dose, lumbar lordosis, incidence of complications, or need for reoperation, 20 while a study by Fayed et al showed that lateral position nailing had a higher error rate. 21 In addition, most studies used only postoperative CT as a criterion for the presence and extent of bias. In clinical practice, for intraoperative misaligned K-wires, the surgeon may choose to realign or change to freehand placement.…”
Section: Screw Accuracymentioning
confidence: 99%
“…The orthopedic surgical robot has the advantages of safety, accuracy, less radiation, and a shorter learning curve, and more and more surgeons have begun to perform robot-assisted surgeries [ 17 ]. In spinal surgeries, robot assistance is often adopted for pedicle screw insertion, navigation, and positioning in vertebroplasty [ 18 , 19 , 20 , 21 , 22 ]. Therefore, the accuracy of robot navigation and positioning directly affects the quality of spinal surgeries.…”
Section: Discussionmentioning
confidence: 99%